Poultry Farming in the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Manual of poultry production in the tropics. 1987. CAB International, Oxon, 118 pp. ISBN 0 85198 590 4